Adsorption-catalysis bifunctional coupling composite water treatment material and preparation method thereof
Patent Information
- Application Number
- CN202611469608.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]为了解决现有简单物理混合体系中吸附位点与催化位点空间隔离导致传质路径过长、界面电荷转移效率低、催化层易堵塞吸附孔道以及材料回收困难等技术缺陷,本发明提供了一种吸附-催化双功能耦合的复合水处理材料,该材料能够形成稳定吸附富集-界面转化-介质再生-磁分离回用循环,有效提高低浓度污染物处理效率
[0023]多孔吸附中间层能够将低浓度污染物富集至光催化活性界面附近,缩短污染物由水相向催化位点迁移的距离,提高低浓度条件下的表观反应速率;与石墨相氮化碳形成界面接触,助催化金属纳米颗粒进一步提供电子捕获和表面反应位点,从而拓展光响应并降低光生载流子的无效复合;光催化氧化能够分解占据吸附位点的有机污染物,使有机物吸附容量得到部分或大部分恢复,减少频繁热再生或高浓度化学脱附的需求。
Smart Images

Figure CN122974276A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of environmental engineering, water pollution control and functional materials technology, specifically to a composite water treatment material with adsorption-catalysis dual-function coupling and its preparation method. Background Technology
[0002] Low-concentration recalcitrant organic pollutants and heavy metal pollutants such as chromium, mercury, and lead are characterized by high toxicity, strong environmental persistence, and great difficulty in treatment. Traditional adsorption processes such as activated carbon can reduce the concentration of pollutants in the aqueous phase, but they mainly achieve the transfer of pollutants from the aqueous phase to the solid phase. After the adsorption material reaches saturation, it needs to be treated by thermal regeneration, chemical desorption, or incineration, which not only leads to complicated subsequent treatment processes, but also easily causes secondary pollution risks such as regeneration waste liquid or waste gas.
[0003] Photocatalytic oxidation can utilize photogenerated holes and reactive species such as hydroxyl radicals and superoxide radicals to degrade organic pollutants. However, at low pollutant concentrations, the effective collision and mass transfer rates on the catalyst surface are limited. Powdered photocatalysts also suffer from poor settling performance, difficulty in solid-liquid separation, and catalyst loss. For heavy metal pollutants, photocatalysis can only change the valence state or deposition form of some metal elements, but cannot eliminate the metal elements themselves, still requiring fixation, concentration, and recovery steps.
[0004] Existing simple physical mixing systems of adsorption materials and photocatalytic materials usually suffer from problems such as excessively long mass transfer paths due to the spatial physical isolation between adsorption sites and catalytic sites, low interfacial charge transfer efficiency, blockage of adsorption channels by the catalytic layer, and difficulty in material recovery, making it difficult to form a stable cycle of adsorption enrichment-interfacial conversion-media regeneration-magnetic separation and reuse.
[0005] Therefore, there is a need to provide a composite water treatment material that is structurally stable, has open pores, has interfacial charge transfer capabilities, and can be rapidly magnetically separated. This material should be integrated with a phased water treatment process to improve the treatment efficiency of low-concentration pollutants while separately managing the mineralization of organic pollutants and the fixation and recovery of heavy metals. Summary of the Invention
[0006] To address the shortcomings of existing simple physical mixing systems, such as excessively long mass transfer paths due to spatial isolation between adsorption and catalytic sites, low interfacial charge transfer efficiency, easy clogging of adsorption channels by the catalytic layer, and difficulties in material recovery, this invention provides a composite water treatment material with adsorption-catalysis dual-functional coupling. This material can form a stable cycle of adsorption enrichment, interfacial transformation, media regeneration, and magnetic separation for reuse, effectively improving the treatment efficiency of low-concentration pollutants. The specific technical solution is as follows:
[0007] A composite water treatment material with adsorption-catalysis dual-functional coupling comprises, from the inside out, a magnetic core, an inorganic protective isolation layer, a porous adsorption intermediate layer, and a porous photocatalytic heterojunction outer layer; the magnetic core is... , Or a combination of both; the inorganic protective isolation layer is dense. or layer;
[0008] The porous adsorption intermediate layer is a mesoporous carbon or a nitrogen-containing mesoporous carbon composite layer; the outer layer of the porous photocatalytic heterojunction includes defect states. Where 0 < x < 0.5, nanocrystals and graphitic carbon nitride nanosheets, the Nanocrystals are distributed on the outer surface and mesopore entrance of the porous adsorption intermediate layer, and form interfacial contact with the graphitic carbon nitride nanosheets.
[0009] Preferably, the magnetic core is a magnetic nanoparticle with a particle size of 5-30 nm or a magnetic particle cluster with a particle size of 100-800 nm formed by the magnetic nanoparticle; the thickness of the inorganic protective isolation layer is 5-50 nm; and the pore size of the porous adsorption intermediate layer is 2-20 nm, and the layer thickness is 30-300 nm.
[0010] Preferably, the The nanocrystals have a particle size of 5-30 nm. The nanocrystals account for 8%-35% of the total mass of the composite water treatment material, and the graphite-phase carbon nitride nanosheets account for 1%-12% of the total mass of the composite water treatment material; the specific surface area of the composite water treatment material is 300-900 m² / g, the pore volume is 0.2-1.2 cm³ / g, and the saturation magnetization is 10-45 emu / g.
[0011] Preferably, the outer layer of the porous photocatalytic heterojunction is further loaded with co-catalytic metal nanoparticles formed by Au, Pt, Ag or combinations thereof; the particle size of the co-catalytic metal nanoparticles is 2-10 nm, and the loading amount is 0.05%-1.5% of the total mass of the composite water treatment material.
[0012] This invention also provides a method for preparing a composite water treatment material, comprising the following steps:
[0013] Preparation of magnetic core: Sodium acetate and polyethylene glycol were added to ethylene glycol, stirred and dispersed, then transferred to a high-pressure reactor and reacted at 200°C for 10 hours. After cooling, magnetic separation and washing were performed to obtain... Magnetic particle clusters, or further obtained by calcination in air. Magnetic particle clusters;
[0014] Coating and protective isolation layer: The magnetic particle clusters are dispersed in a mixture of ethanol, water and ammonia, and tetraethyl orthosilicate or aluminum isopropoxide is added. The mixture is reacted at 20-40℃ for 4-12 hours. After magnetic separation and washing, magnetic particle clusters coated with the inorganic protective isolation layer are obtained.
[0015] Construction of the adsorption layer: The magnetic particle clusters coated with the inorganic protective isolation layer are mixed with resorcinol, formaldehyde, optionally melamine or urea as nitrogen source and block copolymer soft template. The mixture is subjected to polycondensation at 20-40℃, aging at 60-90℃, washing and drying under weakly alkaline conditions with a pH of 8.0-9.0. The mixture is then heated to 500-600℃ at 1-3℃ / min and held for 2-4h under nitrogen protection for carbonization. After removing the soft template, mesoporous carbon or nitrogen-containing mesoporous carbon composite particles are obtained.
[0016] Supported heterojunction outer layer: Titanium alkoxide is hydrolyzed on the surface of the mesoporous carbon or nitrogen-containing mesoporous carbon composite particles, followed by hydrothermal treatment at 140-180℃ for 4-12 hours, and then heat-treated in nitrogen at 250-350℃ for 1-3 hours to obtain... Composite particles; for the aforementioned The composite particles were reduced in the liquid phase to obtain a surface-loaded defect state. The composite water treatment material is obtained by ultrasonically dispersing and stirring the composite particles of nanocrystals with graphitic carbon nitride nanosheets in a solvent, where 0 < x < 0.5.
[0017] Preferably, the ammonia solution has a mass fraction of 20%-30%; the magnetic particle clusters are ultrasonically dispersed in a mixture of ethanol, water, and ammonia solution, and then tetraethyl orthosilicate or aluminum isopropoxide is added dropwise; the tetraethyl orthosilicate or aluminum isopropoxide is added continuously or in stages to obtain a dense layer with a thickness of 5-50 nm. or Protective isolation layer.
[0018] Preferably, the soft template is removed by immersion in ethanol or an organic solvent before carbonization, and by solid-liquid separation and repeated washing; or the soft template is removed by thermal decomposition during carbonization, and impurities are removed by washing with ethanol or deionized water after carbonization.
[0019] Preferably, the titanium alkoxide is tetrabutyl titanate or titanium isopropoxide; the titanium alkoxide is pre-dissolved in ethanol and added dropwise to the ethanol dispersion of the mesoporous carbon or nitrogen-containing mesoporous carbon composite particles; simultaneously, a separately prepared ethanol solution containing water and acetic acid is added dropwise.
[0020] Preferably, the liquid-phase reduction uses a concentration of 0.05-0.5 mol / L. The aqueous solution is treated at 40-80℃ for 0.5-3h; after reduction, it is washed multiple times with deionized water until the washing solution is neutral; the graphite phase carbon nitride nanosheets are obtained by calcining melamine or urea at 500-550℃ and then performing liquid-phase ultrasonic exfoliation.
[0021] Preferably, the method further includes a step of loading a co-catalytic metal by photodeposition: dispersing the mixed assembly material in an aqueous-alcohol solution containing chloroauric acid, chloroplatinic acid or silver nitrate, using ethanol or methanol as a sacrificial agent, performing photodeposition under inert gas protection, performing magnetic separation and washing, and drying under vacuum or nitrogen at 60-100°C.
[0022] The beneficial effects of this invention are as follows:
[0023] The porous adsorption intermediate layer can enrich low-concentration pollutants near the photocatalytic active interface, shorten the distance that pollutants migrate from the aqueous phase to the catalytic site, and improve the apparent reaction rate under low concentration conditions. The interfacial contact between the metal nanoparticles and the graphitic carbon nitride further provides electron capture and surface reaction sites, thereby expanding the photoresponse and reducing the ineffective recombination of photogenerated carriers. Photocatalytic oxidation can decompose organic pollutants occupying adsorption sites, so that the adsorption capacity of organic matter can be partially or mostly restored, reducing the need for frequent thermal regeneration or high-concentration chemical desorption. Detailed Implementation
[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below; the described embodiments are some embodiments of the present invention, but not all embodiments; based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] Example 1:
[0026] This embodiment provides an adsorption-catalysis bifunctional coupled composite water treatment material and its preparation method. The preparation method of the composite water treatment material includes the following steps: preparing a magnetic core: adding 1.35g of ferric chloride hexahydrate, 3.6g of sodium acetate and 1.0g of polyethylene glycol to 40mL of ethylene glycol, stirring and dispersing, reacting at 200℃ for 10h, cooling, and then performing magnetic separation and washing to obtain... Magnetic particle clusters, with a magnetic core having a saturation magnetization of 10-45 emu / g, are used to ensure subsequent magnetic separation;
[0027] Coating and protective isolation layer: 1.0g Magnetic particle clusters were dispersed in a mixture of 100 mL ethanol, 20 mL water, and 5 mL ammonia solution (25% by mass). After ultrasonic dispersion, 2 mL of tetraethyl orthosilicate was added dropwise, and the mixture was reacted at 30 °C for 8 h. Following magnetic separation and washing, the desired product was obtained. Particles, As an inorganic protective isolation layer, the layer can effectively prevent the magnetic core from dissolving in acidic or oxidizing environments, thus protecting the magnetic properties.
[0028] Construction of the adsorption layer: 1.2g The particles were mixed with 0.5g resorcinol, 0.7mL formaldehyde and 1.0g block copolymer soft template. Under weakly alkaline conditions, ammonia was added to adjust the pH to 8.5. Polycondensation was carried out at 30℃ for 12h, aging at 80℃ for 24h, washing and drying were performed, and carbonization was carried out under nitrogen protection by heating to 550℃ at 2℃ / min and holding for 3h. After removing the soft template, mesoporous carbon composite particles were obtained. The mesoporous carbon layer can provide abundant specific surface area and pores for enriching organic pollutants.
[0029] The outer layer of the heterojunction was loaded as follows: 2 mL of titanium alkoxide (tetrabutyl titanate in this example) was pre-dissolved in 10 mL of ethanol and added dropwise to 50 mL of ethanol dispersion containing 1.0 g of mesoporous carbon composite particles. This was done simultaneously with an ethanol solution containing water and acetic acid. The titanium alkoxide was hydrolyzed on the surface of the mesoporous carbon composite particles. After hydrothermal treatment at 160 °C for 8 h, the mixture was then heat-treated at 300 °C for 2 h under nitrogen to obtain the desired product. Composite particles;
[0030] For 1.0g The composite particles were prepared using 50 mL of a 0.2 mol / L solution. The aqueous solution was subjected to liquid-phase reduction at 60℃ for 2 hours, followed by washing until the conductivity and pH stabilized, yielding a surface rich in... The defective state reduction intermediate was used to promote the separation of photogenerated carriers. 0.5 g of the reduction product and 0.05 g-5 g of melamine were calcined at 550 °C for 2 h, and then ultrasonically exfoliated in an aqueous solution for 10 h to obtain graphitic carbon nitride nanosheets. The graphitic carbon nitride nanosheets were ultrasonically dispersed and mixed in deionized water to obtain a composite water treatment material.
[0031] The material's BET specific surface area is 580. The pore volume is 0.65. The material has a saturation magnetization of 25 emu / g, an inorganic protective isolation layer thickness of 15 nm, and a porous adsorption intermediate layer with a pore size of 8 nm and a layer thickness of 150 nm. The specific steps involved in the material performance testing are as follows:
[0032] S1 Influent Conditioning: Simulated wastewater containing bisphenol A and hexavalent chromium is introduced into the conditioning unit to remove suspended solids with a particle size greater than 0.5 mm and adjust the pH of the wastewater to 5.5;
[0033] S2 Dark Adsorption and Enrichment: The adjusted wastewater is sent into a light-dark alternating reactor, and composite water treatment material is added to a concentration of 1.0 g / L. The mixture is circulated and stirred for 30 min under the condition of turning off the light source, so that bisphenol A and hexavalent chromium are enriched on the surface and in the pores of the medium.
[0034] S3 photocatalytic conversion and organic adsorption site regeneration: A light-emitting diode (LED) light source with a wavelength range of 365-450 nm is activated, with an incident light intensity of 60 mM. First, nitrogen gas is introduced to maintain dissolved oxygen at 0.5-1.0 mg / L for 20 minutes. Then, air is introduced to maintain dissolved oxygen at 4-6 mg / L. The light is then applied for another 70 minutes to oxidize and decompose the adsorbed bisphenol A and reduce the adsorbed hexavalent chromium to trivalent chromium.
[0035] S4 Heavy Metal Fixation: Adjust the pH of the system to 7.5-8.0 and continue stirring for 10 min to fix trivalent chromium through surface complexation and hydroxide deposition;
[0036] S5 Magnetic Separation Effluent: After aeration is stopped, the high gradient magnetic separation component is turned on, and separation is carried out for 30 seconds under a magnetic induction intensity of 0.5T. The medium is recovered and the treated water is discharged. S6 Medium Recirculation: After power is cut off, the medium is sent back to the reactor by reverse water flow to enter the next cycle.
[0037] Example 2:
[0038] Compared with Example 1, this embodiment aims to verify the lower limit of the relevant preparation parameter range, the replacement of similar media materials, and the loading of co-catalyst metals; and the composite water treatment material is replaced with a magnetic core with a particle size of approximately 20 nm. The inorganic protective isolation layer is approximately 10 nm thick. The adsorption intermediate layer is nitrogen-containing mesoporous carbon with a thickness of about 100 nm;
[0039] The preparation method of the composite water treatment material is similar to the process flow of Example 1, with specific changes including: controlling the reaction conditions at 180°C for 6 hours during the preparation of the magnetic core, and oxidizing it by calcination at 250°C for 2 hours in air atmosphere. When coating the protective isolation layer, 2.5g of aluminum isopropoxide was used instead of tetraethyl orthosilicate. The remaining hydrolysis medium and ammonia water dosage were the same as in Example 1. The reaction was carried out at 20°C for 4 hours. ;
[0040] During the construction of the adsorption layer, 0.2 g of melamine was added to the soft template mixture as a nitrogen source, and carbonization was carried out by raising the temperature to 500℃ at a rate of 1℃ / min and holding it at that temperature for 2 hours. When loading the heterojunction outer layer, hydrothermal treatment was performed at 140℃ for 4 hours, followed by heat treatment at 250℃ in nitrogen for 1 hour. Liquid-phase reduction was carried out using a concentration of 0.05 mol / L... The composite water treatment material was treated at 40℃ for 0.5 hours; it was also loaded with a co-catalyst metal via photodeposition.
[0041] 1.0 g of the assembled material was dispersed in 100 mL of a 0.25 mmol / L solution. In an aqueous-alcohol solution, using ethanol as a sacrificial agent, photodeposition was performed for 2 hours under inert gas protection using a 300W xenon lamp. Following magnetic separation and washing, the material was vacuum dried at 80°C to obtain a composite water treatment material loaded with Au nanoparticles. The co-catalyst metal nanoparticles had a particle size of 5 nm and a loading of 0.5% of the total mass of the composite water treatment material.
[0042] The material's BET specific surface area is 450. The pore volume is 0.4. The saturation magnetization is 35 emu / g; the process steps of each circulating water treatment method in this embodiment are the same as in Embodiment 1, with the specific time and concentration parameters adjusted as follows:
[0043] S1 Influent Adjustment: Adjust the pH of the wastewater to 5.5;
[0044] S2 Dark-state adsorption enrichment: The concentration of the composite water treatment material was 1.0 g / L, and the dark-state adsorption lasted for 30 min.
[0045] S3 photocatalytic conversion and organic adsorption site regeneration: light intensity 60m During the low-oxygen phase, dissolved oxygen was maintained at 0.5-1.0 mg / L for 20 minutes; during the oxygen-containing phase, dissolved oxygen was maintained at 4-6 mg / L, and illumination continued for 100 minutes, for a total illumination time of 120 minutes.
[0046] S4 Heavy Metal Immobilization: Adjust the system pH to 7.5-8.0;
[0047] S5 magnetic separation water: separation for 30s under a magnetic induction intensity of 0.5T;
[0048] S6 Media Return: The media is returned to the reactor using reverse water flow.
[0049] Example 3:
[0050] Compared with Example 1, this embodiment mainly changes the amount of medium added, the adsorption time, and the magnetic separation conditions, while the other steps are the same;
[0051] S1 Influent Adjustment: Adjust the pH of the wastewater to 6.5;
[0052] S2 Dark-state adsorption enrichment: The concentration of the composite water treatment material was 2.0 g / L, and the dark-state adsorption lasted for 60 min;
[0053] S3 photocatalytic conversion and organic adsorption site regeneration: light intensity 100m First, nitrogen gas is introduced to maintain dissolved oxygen at 1.0-1.5 mg / L during the low-oxygen phase for 5 minutes; then air is switched to maintain dissolved oxygen at 6-8 mg / L during the oxygen-containing phase, and light is continued for 15 minutes, for a total light exposure time of 20 minutes. This process oxidizes and decomposes adsorbed bisphenol A and reduces adsorbed hexavalent chromium to trivalent chromium.
[0054] S4 Heavy Metal Immobilization: The system pH was adjusted to 8.0;
[0055] S5 magnetic separation water: separation for 10s under a magnetic induction intensity of 1.0T;
[0056] S6 Media Return: The media is returned to the reactor using reverse water flow.
[0057] Example 4:
[0058] Compared with Example 1, this embodiment aims to verify the upper limit of the relevant preparation parameter range, so as to evaluate the specific impact of the upper limit of the parameters on the decontamination performance of the composite water treatment material, and to prove the rationality of the range of the present invention; in the preparation method of the composite water treatment material, the parameters are adjusted as follows: when preparing the magnetic core, the reaction is carried out at 220°C for 12 hours; when coating the protective isolation layer, the reaction is carried out at 40°C for 12 hours;
[0059] Carbonization of the adsorption layer was achieved by heating to 600℃ at a rate of 3℃ / min and holding for 4 hours; the outer layer of the heterojunction was subjected to hydrothermal treatment at 180℃ for 12 hours, followed by heat treatment at 350℃ in nitrogen for 3 hours, and liquid-phase reduction was performed using a 0.5mol / L solution. The water was treated at 80℃ for 3 hours; all parameters of the circulating water treatment method were kept consistent with those in Example 1.
[0060] S1 Influent Adjustment: Adjust the pH of the wastewater to 5.5;
[0061] S2 Dark-state adsorption enrichment: The concentration of the composite water treatment material was 1.0 g / L, and the dark-state adsorption lasted for 30 min.
[0062] S3 photocatalytic conversion and organic adsorption site regeneration: light intensity 60m During the low-oxygen phase, dissolved oxygen was maintained at 0.5-1.0 mg / L for 20 minutes. During the oxygen-containing phase, dissolved oxygen was maintained at 4-6 mg / L. Irradiation continued for 80 minutes (i.e., a total of 100 minutes of illumination). The reaction temperature was strictly controlled at 25℃.
[0063] S4 Heavy Metal Immobilization: Adjust the system pH to 7.5-8.0;
[0064] S5 magnetic separation water: separation for 30s under a magnetic induction intensity of 0.5T;
[0065] S6 Media Return: The media is returned to the reactor by a combination of air and water flushing.
[0066] Comparative Example 1:
[0067] The difference between this comparative example and Example 1 is that step S2, dark-state adsorption and enrichment, is omitted; all other operating steps and process parameters are exactly the same as in Example 1.
[0068] Comparative Example 2:
[0069] The difference between this comparative example and Example 1 is that the outer layer of the composite water treatment material is replaced with a material containing only... The photocatalytic layer of the particles does not contain graphite-phase carbon nitride nanosheets, and the other operating steps and process parameters are exactly the same as in Example 1.
[0070] Comparative Example 3:
[0071] The difference between this comparative example and Example 1 is that the high gradient magnetic separation condition in step S5 is replaced by 0.05T instead of 0.5T, while the other operating steps and process parameters are exactly the same as in Example 1.
[0072] Comparative Example 4:
[0073] The difference between this comparative example and Example 1 is that the low-oxygen stage in step S3 is directly omitted, and the dissolved oxygen is maintained at 4-6 mg / L throughout the light exposure period. Other operating steps and process parameters are exactly the same as in Example 1.
[0074] Comparative Example 5:
[0075] The difference between this comparative example and Example 1 is that the concentration of the composite water treatment material added in step S2 is replaced by 0.2 g / L instead of 1.0 g / L. The other operating steps and process parameters are exactly the same as in Example 1.
[0076] Performance Tests and Data Sheets:
[0077] In this invention, the particle size, layer thickness, and pore size of the magnetic core and composite material were measured using transmission electron microscopy or scanning electron microscopy; the specific surface area and pore volume were measured using nitrogen adsorption-desorption isotherms; and the saturation magnetization was measured using a vibrating sample magnetometer.
[0078] Using the same initial water sample conditions, the simulated wastewater volume for each test was 500 mL, placed in a jacketed double-layered glass reactor with an effective volume of 1 L. The initial concentration of bisphenol A was set at 20 mg / L, and the initial concentration of hexavalent chromium was set at 10 mg / L. The temperature was controlled at 25℃ for batch treatment tests. Bisphenol A was detected by high performance liquid chromatography with an ultraviolet detector at a wavelength of 278 nm. Hexavalent chromium was detected by diphenylcarbazide spectrophotometry at a wavelength of 540 nm. Total organic carbon was determined by a total organic carbon analyzer to characterize the degree of organic mineralization. Total chromium was characterized by atomic absorption spectrometry to characterize the heavy metal removal effect. The media loss rate was calculated by combining the turbidity of the effluent after solid-liquid separation and the particle recovery rate. The calculation formula was: Media loss rate (%) = (1 - actual recovered dry media mass after magnetic separation / initial added dry media mass) × 100%, combined with effluent turbidity correction. Each test was repeated 3 times, and the average value was taken.
[0079] Table 1. Performance test results of each embodiment and comparative example.
[0080]
[0081] As can be seen from the comparison of the test results of Example 1 and Comparative Example 1 in Table 1, omitting the dark adsorption and enrichment step resulted in a significant decrease in the removal rates of bisphenol A, total organic carbon, and hexavalent chromium. Since the pollutants were not pre-enriched to the surface of the medium and near the pore inlet, the probability of interfacial contact during the illumination stage decreased, and the efficiency of photogenerated carriers in dealing with low-concentration pollutants decreased. Therefore, the ability to degrade organic matter and convert heavy metals was simultaneously weakened.
[0082] As can be seen from the comparison of the test results of Example 1 and Comparative Example 2 in Table 1, replacing the outer layer with only containing After particle removal, the removal rates of bisphenol A and total organic carbon decreased; after the loss of graphitic carbon nitride, The interfacial charge transfer conditions between the second component and the second component are weakened, making it easier for photogenerated electrons and holes to recombine in the bulk phase. This reduces the oxidation rate of adsorbed organic pollutants and consequently decreases the regeneration rate of the medium surface.
[0083] As can be seen from the comparison of the test results of Example 1 and Comparative Example 3 in Table 1, after reducing the magnetic induction intensity of magnetic separation, the media loss rate increased significantly; the magnetic force's ability to retain particles weakened, and fine particles were more likely to migrate with the effluent, resulting in a reduction in the amount of return media, a decrease in the concentration of effective active materials in the reactor, and an impact on the subsequent circulation treatment effect.
[0084] As can be seen from the comparison of the test results of Example 1 and Comparative Example 4 in Table 1, the removal rate of hexavalent chromium decreased after omitting the low-oxygen stage; when the dissolved oxygen is too high, it will compete with photogenerated electrons and reduce the probability of hexavalent chromium accepting electrons for reduction, thus limiting the conversion of heavy metal valence states and reducing the amount of trivalent chromium formed in the subsequent fixation process.
[0085] As can be seen from the comparison of the test results of Example 1 and Comparative Example 5 in Table 1, after reducing the concentration of the medium, the removal rates of bisphenol A, total organic carbon, and hexavalent chromium all decreased; the number of adsorption sites and photocatalytic interfaces available per unit volume of water decreased, the pollutant enrichment capacity decreased, resulting in a decrease in the interfacial reaction flux during the illumination stage, and the overall treatment efficiency weakened accordingly.
[0086] The above are merely specific embodiments of the present invention and are not intended to limit the present invention in any other way. Any person skilled in the art may make changes or modifications to the above-disclosed technical content to create equivalent embodiments for application in other fields. However, any conventional modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the technical solution of the present invention shall still fall within the protection scope of the technical solution of the present invention.
Claims
1. A composite water treatment material with adsorption-catalysis bifunctional coupling, characterized in that, It includes, from the inside out, a magnetic core, an inorganic protective isolation layer, a porous adsorption intermediate layer, and a porous photocatalytic heterojunction outer layer; the magnetic core is... , Or a combination of both; the inorganic protective isolation layer is dense. or The porous adsorption intermediate layer is a mesoporous carbon or nitrogen-containing mesoporous carbon composite layer. The outer layer of the porous photocatalytic heterojunction includes defect states. Where 0 < x < 0.5, nanocrystals and graphitic carbon nitride nanosheets, the Nanocrystals are distributed on the outer surface and mesopore entrance of the porous adsorption intermediate layer, and form interfacial contact with the graphitic carbon nitride nanosheets.
2. The composite water treatment material according to claim 1, characterized in that, The magnetic core is a magnetic nanoparticle with a particle size of 5-30 nm or a magnetic particle cluster with a particle size of 100-800 nm formed by the magnetic nanoparticle; the thickness of the inorganic protective isolation layer is 5-50 nm; the pore size of the porous adsorption intermediate layer is 2-20 nm and the layer thickness is 30-300 nm.
3. The composite water treatment material according to claim 1, characterized in that, The The nanocrystals have a particle size of 5-30 nm. The nanocrystals account for 8%-35% of the total mass of the composite water treatment material, and the graphite-phase carbon nitride nanosheets account for 1%-12% of the total mass of the composite water treatment material; the specific surface area of the composite water treatment material is 300-900 m² / g, the pore volume is 0.2-1.2 cm³ / g, and the saturation magnetization is 10-45 emu / g.
4. The composite water treatment material according to claim 1, characterized in that, The outer layer of the porous photocatalytic heterojunction is further loaded with co-catalytic metal nanoparticles formed by Au, Pt, Ag or combinations thereof; the particle size of the co-catalytic metal nanoparticles is 2-10 nm, and the loading amount is 0.05%-1.5% of the total mass of the composite water treatment material.
5. A method for preparing a composite water treatment material as described in any one of claims 1-4, characterized in that, Includes the following steps, Preparation of magnetic core: Sodium acetate and polyethylene glycol were added to ethylene glycol, stirred and dispersed, then transferred to a high-pressure reactor and reacted at 200°C for 10 hours. After cooling, magnetic separation and washing were performed to obtain... Magnetic particle clusters, or further obtained by calcination in air. Magnetic particle clusters; Coating and protective isolation layer: The magnetic particle clusters are dispersed in a mixture of ethanol, water and ammonia, and tetraethyl orthosilicate or aluminum isopropoxide is added. The mixture is reacted at 20-40°C for 4-12 hours. After magnetic separation and washing, magnetic particle clusters coated with the inorganic protective isolation layer are obtained. Construction of the adsorption layer: The magnetic particle clusters coated with the inorganic protective isolation layer are mixed with resorcinol, formaldehyde, optionally melamine or urea as nitrogen source and block copolymer soft template. The mixture is subjected to polycondensation at 20-40℃, aging at 60-90℃, washing and drying under weakly alkaline conditions with a pH of 8.0-9.
0. The mixture is then heated to 500-600℃ at 1-3℃ / min and held for 2-4h under nitrogen protection for carbonization. After removing the soft template, mesoporous carbon or nitrogen-containing mesoporous carbon composite particles are obtained. Supported heterojunction outer layer: Titanium alkoxide is hydrolyzed on the surface of the mesoporous carbon or nitrogen-containing mesoporous carbon composite particles, followed by hydrothermal treatment at 140-180℃ for 4-12 hours, and then heat-treated in nitrogen at 250-350℃ for 1-3 hours to obtain... Composite particles; for the aforementioned The composite particles were reduced in the liquid phase to obtain a surface-loaded defect state. The composite water treatment material is obtained by ultrasonically dispersing and stirring the composite particles of nanocrystals with graphitic carbon nitride nanosheets in a solvent, where 0 < x < 0.
5.
6. The preparation method according to claim 5, characterized in that, The ammonia solution has a mass fraction of 20%-30%; the magnetic particle clusters are ultrasonically dispersed in a mixture of ethanol, water, and ammonia solution, and then tetraethyl orthosilicate or aluminum isopropoxide is added dropwise; the tetraethyl orthosilicate or aluminum isopropoxide is added continuously or in stages to obtain a dense layer with a thickness of 5-50 nm. or Protective isolation layer.
7. The preparation method according to claim 5, characterized in that, Before carbonization, the soft template is removed by immersion in ethanol or organic solvent and by solid-liquid separation and repeated washing; or the soft template is removed by thermal decomposition during carbonization and then washed with ethanol or deionized water after carbonization to remove impurities.
8. The preparation method according to claim 5, characterized in that, The titanium alkoxide is tetrabutyl titanate or titanium isopropoxide; the titanium alkoxide is pre-dissolved in ethanol and added dropwise to the ethanol dispersion of the mesoporous carbon or nitrogen-containing mesoporous carbon composite particles; at the same time, a separately prepared ethanol solution containing water and acetic acid is added dropwise.
9. The preparation method according to claim 5, characterized in that, The liquid-phase reduction uses a concentration of 0.05-0.5 mol / L. The aqueous solution is treated at 40-80℃ for 0.5-3h; after reduction, it is washed multiple times with deionized water until the washing solution is neutral; the graphite phase carbon nitride nanosheets are obtained by calcining melamine or urea at 500-550℃ and then performing liquid-phase ultrasonic exfoliation.
10. The preparation method according to claim 5, characterized in that, It also includes the step of loading co-catalytic metals by photodeposition: dispersing the mixed assembly material in an aqueous-alcohol solution containing chloroauric acid, chloroplatinic acid or silver nitrate, using ethanol or methanol as a sacrificial agent, performing photodeposition under inert gas protection, performing magnetic separation and washing, and drying under vacuum or nitrogen at 60-100℃.